TERAPI PENYAKIT HATI MENURUT IBN TAIMIYAH DALAM PERSPEKTIF BIMBINGAN KONSELING ISLAM - Kholil Lur Rochman (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2009)
According to Ibnu Taimiyah, spiritual disorder (penyakit hati) is a condition which can destroyhuman imagination and desire. Spiritual disorder cannot be physically seen and do not cause physicalpains. It includes the decrease of one’s belief in Allah, His messengers and the Judgement day, riya(feeling proud of demonstrating self’s good deeds), being arrogant, stingy, jealous, hedonistic, havingtoo much imagination, forgetting death and the Jugdement day, and some others. This condition canbe recognized by the occurrence of laziness to do good deeds, hedonistic mind set, and the like. Ifsomeone shows those signs it is really necessary for them to handle this condition. Islamic counselinghelp people to handle such condition by giving continuous, directed, and systematic treatment todevelop their spiritual potentials optimally. An Islamic counselor can help a client to face and solve theirspiritual problems to live in a harmonious life